PENGGUNAAN EKSTRAKSI FASA PADAT UNTUK ANALISIS TETRASIKLIN DALAM CONTOH UDANG - Evita Boes; Julia Kantasubrata; A. T. Karossi (Research Center for Chemistry - LIPI, 1993)
A great quantity of Indonesian frozen prawns were exported to Japan and America. Unfortunately these products have often been rejected due to their content of tetracycline derivative residues. Qualitative analysis of frozen prawn samples being exported by means of HPLC, indicated that they are contaminated by oxytetracycline and tetracycline residues. A problem of quantitative analysis of such residues could be due to several peaks of the matrix being eluted closely to the peaks of the tetracycline derivatives. An experiment was carried out to eliminate the peaks of the matrix origin using SPE (Solid Phase Extraction) in order to quantify the derivatives more accurately. Application of SPE in the sample pretreatment is useful not only for separating the solute being analyzed from the matrixs, but also for concentrating the tetracycline derivatives of the extract. The recovery of SPE column elution process was about 90% and the SPE octadecyl (1 ml) column capacity for oxytetracycline, tetracycline, demeclocycline and doxycycline i.e. 2.4-7.9 ug; 3.5-11.8 ug; 3.4-11.2 ug and 17.3-57.5 ug respectively.